1999
DOI: 10.1038/sj.bmt.1701733
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal photopheresis (ECP) in the treatment of chronic graft-versus-host disease (GVHD)

Abstract: Summary:The aim of our study was to assess the efficacy of extracorporeal photopheresis (ECP) in chronic graft-versushost disease (GVHD). Eleven patients with chronic cutaneous GVHD were studied. Four had mucosal involvement and five had pulmonary involvement. All had failed to improve on first-and second-line therapy. Three patients received ECP alone; the remainder continued to receive steroids and/or immunosuppressive therapy. Patients received ECP twice monthly for 4 months and then once monthly for 3 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
84
3
7

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(99 citation statements)
references
References 19 publications
5
84
3
7
Order By: Relevance
“…43 Two recent studies reported results of ECP in 11 and 15 patients, respectively. 44,45 All patients had failed first-and second-line therapies, including corticosteroids and CsA. In one study ECP therapy was initiated late after the onset of cGVHD (median 510 days), while in the other it was initiated earlier (median 178 days).…”
Section: Clinical Efficacy Of Ecp In Cgvhdmentioning
confidence: 99%
“…43 Two recent studies reported results of ECP in 11 and 15 patients, respectively. 44,45 All patients had failed first-and second-line therapies, including corticosteroids and CsA. In one study ECP therapy was initiated late after the onset of cGVHD (median 510 days), while in the other it was initiated earlier (median 178 days).…”
Section: Clinical Efficacy Of Ecp In Cgvhdmentioning
confidence: 99%
“…Our group and others have previously reported the efficacy of ECP in the management of cGVHD in retrospective studies. [2][3][4][5] To date, there are only a few prospective studies of ECP for this condition [6][7][8][9] and one randomised prospective trial. 10 In addition, there are few data on the effect of ECP on quality of life (QoL) in patients with cGVHD.…”
Section: Introductionmentioning
confidence: 99%
“…Three publications were cited as specific support in considering ECP for first-line treatment of chronic GVHD. [12][13][14] In our view, the evidence from these publications does not support this endorsement. One of the three studies was a single-arm prospective clinical trial evaluating the safety and efficacy of ECP for treatment of chronic GVHD and was not limited to patients with pulmonary involvement.…”
mentioning
confidence: 50%
“…The single study cited by Conference report as support for considering the use of azithromycin in first-line treatment of pulmonary GVHD 15 differs strikingly from the three studies cited as support for considering the use of ECP for the same indication. [12][13][14] The high-quality evidence from the azithromycin study far outweighs the ostensible numerical advantage of the much less persuasive ECP studies. In evaluating the literature, the strength of the evidence is not necessarily related to the number of publications recommending any given treatment.…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation